Uniaxial and Biaxial Response of Anisotropic Polypropylene. Issue 4 (29th May 2020) - Kershah, Tarek; Anderson, Patrick D.; van Breemen, Lambèrt C. A.
Abstract: The response of uniaxial and biaxial anisotropic polypropylene is discussed. A 3D elasto‐viscoplastic constitutive model is developed to account for material anisotropy. The famous Hill's anisotropic yield criterion is combined with the Eyring relation and implemented in a finite element framework to model the response of the polymer during uniaxial loading. An associated viscoplastic flow rule that describes the magnitude and the direction of the viscoplastic flow is incorporated in the model to simulate complex loading conditions. The model quantitatively captures the yield stresses for uniaxial deformation at a given anisotropic state and material orientation. In addition, the results of simulations demonstrate that the constitutive relations qualitatively describe the material deformation during biaxial loading for both isotropic and anisotropic cases. Abstract : This work models the response of an anisotropic polymer during uniaxial and biaxial tensile loading. The model accounts for rate, temperature, and pressure dependencies. It is tested over a range of orientation angles and draw ratios. It can be used to predict the response of anisotropic polymers during complex loading cases such as indentation or scratch testing.